Pengaruh Electronic Word of Mouth, Kualitas Produk, dan Kepuasan terhadap Repurchase Intention pada Produk Somethinc: Studi pada Masyarakat Kota Surabaya - Bernadeth Gabriella Putri Hardianti; Siti Ning Farida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine and analyze the effect of Electronic Word of Mouth, Product Quality, and Satisfaction on Repurchase Intention. This research uses a quantitative approach with an associative research type. The population in this research is Somethinc product customers in Surabaya City. The sample used in this study were 100 respondents, taken using purposive sampling technique with the criteria of Surabaya City residents who are at least 17 years old and have made purchases and have used Somethinc products at least twice. Data analysis techniques in this research consist of validity tests, reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis tests, which are analyzed using the SPSS 26 data processing program. The results of this study indicate that the variables of Electronic Word of Mouth, Product Quality, and Satisfaction simultaneously have a significant effect on Repurchase Intention. Electronic Word of Mouth, Product Quality, and Satisfaction variables partially also have a significant effect on Repurchase Intention.